2015
DOI: 10.1097/rli.0000000000000178
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Magnetic Resonance Imaging and Computed Tomography of the Lung in Patients With Cystic Fibrosis With Regard to Clinical, Laboratory, and Pulmonary Functional Parameters

Abstract: Objective: To evaluate whether magnetic resonance imaging (MRI) is effective as computed tomography (CT) in determining morphologic and functional pulmonary changes in patients with cystic fibrosis (CF) in association with multiple clinical parameters. Materials and Methods: Institutional review board approval and patient written informed consent were obtained. In this prospective study, 30 patients with CF (17 men and 13 women; mean (SD) age, 30.2 (9.2) years; range, 19-52 years) were included. Chest CT was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 41 publications
0
26
0
1
Order By: Relevance
“…In the field of imaging, it has been shown that the presence of mucous plugging impaction with hyperattenuating mucus (HAM) at computed tomography (CT) is a 100% specific criterion of ABPA in THORACIC IMAGING: MR Imaging Diagnosis of Allergic Bronchopulmonary Aspergillosis in Cystic Fibrosis Dournes et al imaging evaluation, readers were asked to assess the presence of mucoid impaction at the lobar level by using a binary scale (present = 1). When a mucoid impaction was considered to be present, readers had to then evaluate whether its signal intensity was similar to that of the previously published "waterlike" MR imaging appearance (ie, hypointensity on T1-weighted images and hyperintensity on T2-weighted images [18,20]) or if it was defined by the novel IMIS sign, which is hyperintense on T1-weighted images and hypointense on T2-weighted images (10).…”
Section: Implication For Patient Carementioning
confidence: 99%
“…In the field of imaging, it has been shown that the presence of mucous plugging impaction with hyperattenuating mucus (HAM) at computed tomography (CT) is a 100% specific criterion of ABPA in THORACIC IMAGING: MR Imaging Diagnosis of Allergic Bronchopulmonary Aspergillosis in Cystic Fibrosis Dournes et al imaging evaluation, readers were asked to assess the presence of mucoid impaction at the lobar level by using a binary scale (present = 1). When a mucoid impaction was considered to be present, readers had to then evaluate whether its signal intensity was similar to that of the previously published "waterlike" MR imaging appearance (ie, hypointensity on T1-weighted images and hyperintensity on T2-weighted images [18,20]) or if it was defined by the novel IMIS sign, which is hyperintense on T1-weighted images and hypointense on T2-weighted images (10).…”
Section: Implication For Patient Carementioning
confidence: 99%
“…Annual radiologic diagnostics are performed with X-ray or computed tomography (CT) scan producing a significant amount of radiation exposure to the patient. Newer techniques such as magnetic resonance imaging (MRI) allow a comparable examination of the lung [9][10][11]. Additionally, the radiology and nuclear medicine service should still include CT scanning, liver ultrasound and dual-energy X-ray absorptiometry (DXA) bone scanning.…”
Section: Management Of Patients With Cystic Fibrosismentioning
confidence: 99%
“…) . Due to this characteristic “increased signal pathology,” these studies found a high concordance between MRI and CT supporting comparable sensitivity in detecting structural abnormalities across a broad spectrum of CF lung disease severity despite apparent differences in spatial resolution . However, a direct comparison of the sensitivity of two techniques to detect mild bronchiectasis in infants and young children with CF is pending.…”
Section: Mri Of Cf Lung Disease: Visualization Of Morphology Perfusimentioning
confidence: 93%
“…Compared to CT imaging, this conventional MRI approach has the apparent limitation of lower spatial resolution. However, a series of studies in older children and adults with CF demonstrated that characteristic abnormalities in CF lung disease such as airway mucus plugging, bronchial wall thickening, and progressive bronchiectasis are reliably detected by MRI . In fact, it was found that the increase in fluid and tissue (and thus proton density) associated with these abnormalities enhances the sensitivity of MRI and facilitates detection of these pathologies in CF lung disease.…”
Section: Mri Of Cf Lung Disease: Visualization Of Morphology Perfusimentioning
confidence: 99%
See 1 more Smart Citation